Mkhaʼ ʼgro Bdud ʼdul drag moʼi chos skor gter gźuṅ : the complete texts of the revealed cycle of teachings of the Lion-Faced Wrathful Ḍākinī - Stag-śam Nus-ldan-rdo-rje, b. 1655 (Topden Tshering ; distributors, Tibetan Bonpo Monastic Centre, 1977)
Rituals of the Nyingmapa tradition of Tibetan Lamaism.